Antifungal activity of commercial ethanolic and aqueous extracts of Brazilian propolis against Candida spp. - S.M.D. Dias; R.T. Gomes; W.K. Santiago; A.M.B. Paula; M.E. Cortés; V.R. Santos (São Paulo State University (UNESP), 2007)
Fourteen commercial ethanolic extracts (EEP) and five aqueous extracts (AEP) of Brazilian propolis were tested for antifungal activity in vitro by employing the agar diffusion assay to determine the susceptibility of Candida spp. Nystatin (100 IU), sterile distilled water and ethanol 93.2ºGL were used as positive, negative and solvent controls. Except for one sample, all EEP tested inhibited the in vitro growth of Candida spp., while the AEP extracts were only weakly inhibitory to the growth of these microorganisms. Four EEP products exhibited inhibition zones similar to those induced by nystatin. It was concluded that the commercial EEP extracts were more effective against Candida spp. than the aqueous extracts. This suggests that EEP could be used as an alternative medicine for the treatment of fungal infections of the oral cavity, such as oral candidosis (thrush) or denture stomatitis.